THE USE OF VISUAL SCAFFOLDING IN HELPING STUDENTS TO LEARN PROCEDURE TEXT - Rika Amelia Arizki (Journal of English Education Program (JEEP), 2016)
This paper deals with the use of visual scaffolding in helping student to learn procedure text. This study was aimed at investigating how the teacher scaffold the student through visual scaffolding in the teaching learning process of procedure text and figuring out the issues encountered by the teacher in applying visual scaffolding. The writer used a case study design as a research design of the study in order to gained the detail information how the use of visual scaffolding in helping students to learn procedure text. The instruments used in this study consisted of two instruments including classroom observation and interview. The results of data analysis showed that the first research question of this study which emphasized on how does the teacher scaffold the student in the teaching learning process of procedure text through visual scaffolding. In this sense, the kinds of scaffolding used by teacher in helping students to learn procedure text was visual scaffolding. Besides, the teacher agreed that the implementation of visual scaffolding should be implemented by each of the English teacher to improve students’ comprehension toward the material in the class.